Effect of Falcaria Vulgaris on Milk Production Parameters in Female Rats' Mammary Glands - Mohammad Reza Salahshoor; Mohammad Mehdi Mohammadi; Shiva Roshankhah; Cyrus Jalili (Tehran University of Medical Sciences, 2019)
Objective: Falcaria Vulgaris (F.Vulgaris) is a multipurpose herb in traditional medicine, containing essential amino acids, vitamins and numerous nutrients. The aim of this study was to determine the effects of F.Vulgaris on the on the milk production parameters in rats. Materials and methods: In this experimental study, 32 wistar female rats were equally divided into 4 groups; group1, control group and group2-4, experimental groups by various doses of F.Vulgaris (20, 50, 100 mg/kg) injected interaperitoneally once a day for 21 consecutive days. The milk production parameters including, diameter and number of alveoli, prolactin hormone level and receptor prolactin (PRLR) gene expression in mammillary gland tissue were measured and compared. Results: The results indicated that F.Vulgaris significantly increased diameter and number of alveoli, prolactin hormone level and PRLR gene expression compared to control group (p < 0.05). Conclusion: F.Vulgaris extract has positive effects on the milk production parameters in mammary glands.